Unlocking the potential of ocean carbon sinks: opportunities and challenges for China’s development - Wang, Yuhui; Bai, Yang (Frontiers in Marine Science, 2025)
As global climate change intensifies, the ocean carbon sink has become a crucial natural mechanism for the international community to mitigate and adapt to climate change, owing to its vast carbon storage capacity and continuous absorption capabilities. China has a wealth of blue carbon ecosystems and recognizes the significant potential of ocean carbon sinks in addressing climate change. Currently, China is incorporating the development of blue carbon into its national strategic development plans. Through policy guidance, scientific and technological support, and pilot demonstrations, the country is actively exploring pathways for the protection, restoration, and sustainable use of blue carbon ecosystems. However, issues such as marine habitat degradation, the absence of specific domestic legislation, and an incomplete standards system for ocean carbon sinks are constraining the effectiveness and market-based development of China’s carbon sinks. To this end, this study proposes that China should actively promote the restoration of marine ecosystems, strengthen domestic legislation for carbon sink trading, and advance the clarification of property rights and the refinement of market rules. At the same time, China should deepen multi-level international cooperation and accelerate the development of a marine carbon sink standard system with Chinese characteristics that aligns with international standards. Through the synergistic advancement of institutions, technology, and cooperation, the full ecological and economic value of ocean carbon sinks can be unlocked, providing robust support for China to achieve its “dual carbon” goals and participate in global climate governance.